Urban Agriculture: The Feasibility of Rooftop Farming in Penang Island, Malaysia - Ee-Wei Then; Meenchee Hong (Journal of Regional and City Planning, 2022)
By 2050, over 60 percent of the global population will live in cities, the majority in high-rise residential buildings. Thus, rooftop farming as part of urban agriculture will be highly important in building sustainable cities. It brings plenty of benefits and opportunities to the environment and society, as well as food supply to urban residents. Singapore, as a land-scarce state, has been very successful in implementing rooftop farming. Even though having a similar geographical condition as Singapore, rooftop farming has yet to be popularized in Penang Island. Rapid development and industrialization are deteriorating air quality and occupying arable land on the island, while the population is highly dependent on imported food. Rooftop farming may be a good option to reduce these problems, seeing there are so many high-rise residential buildings on the island. Therefore, this study aimed to investigate the likelihood of rooftop farming by island residents, and its determinants. Data collected from 323 Penangites that live in high-rise residential buildings revealed that 65 percent of respondents were likely to participate in rooftop farming. The ordered Probit model estimated that awareness of the potential benefits of rooftop farming, environmental knowledge and awareness, environmental consciousness and perception are important factors that determine the likelihood of participating in rooftop farming. The findings of this study may be important for Penang state policy makers, and may also be useful for similar economies globally, to promote, encourage and implement rooftop farming in urban areas, and achieve sustainable cities for future generations.